2024
DOI: 10.1093/jee/toae104
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the susceptibility of Bemisia tabaci Middle East-Asia Minor 1 (Hemiptera: Aleyrodidae) to afidopyropen, cyantraniliprole, dinotefuran, and flupyradifurone in south Florida vegetable fields

Marcelo Dimase,
Bruno Rossitto De Marchi,
Felipe Barreto da Silva
et al.

Abstract: Bemisia tabaci Middle East-Asia Minor 1 (MEAM1) is a significant pest that damages a wide range of high-value vegetable crops in south Florida. This pest has demonstrated the ability to develop resistance to various insecticide groups worldwide. Monitoring the resistance levels of MEAM1 populations and maintaining baseline susceptibility data are crucial for the long-term effectiveness of insecticide management strategies. We conducted serial dilution bioassays on 15 field populations of MEAM1 collected in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, cyantraniliprole may not be sufficient to completely manage MEAM1 populations and TYLCV transmission under higher pest densities [ 18 ]. The rise in resistance to cyantraniliprole is a growing concern in southern U.S. A recent study observed low to moderate levels of MEAM1 resistance to cyantraniliprole in Florida, particularly in Hillsborough County where our trials were conducted [ 23 ]. This emerging resistance is further supported by field scout data from Georgia, indicating a change in the efficacy response to cyantraniliprole and suggesting a potential rise in resistance to this insecticide [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, cyantraniliprole may not be sufficient to completely manage MEAM1 populations and TYLCV transmission under higher pest densities [ 18 ]. The rise in resistance to cyantraniliprole is a growing concern in southern U.S. A recent study observed low to moderate levels of MEAM1 resistance to cyantraniliprole in Florida, particularly in Hillsborough County where our trials were conducted [ 23 ]. This emerging resistance is further supported by field scout data from Georgia, indicating a change in the efficacy response to cyantraniliprole and suggesting a potential rise in resistance to this insecticide [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of afidopyropen against MEAM1 populations has not been extensively evaluated in Florida. However, a recent report indicates low to moderate resistance levels in two MEAM1 populations [ 23 ], including a population from Hillsborough County, the same County where we conducted our trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations